PENERAPAN MODEL ARIMA DALAM PERAMALAN ANAK USIA 5–14 Th YANG TERINFEKSI HIV DI INDONESIA - Wigid Hariadi; Sulantari Sulantari (Fakultas Tarbiyah Universitas Ibrahimy, 2019)
Human Immunodeficiency Virus (HIV) is dangerous diseases for humans, and until now has not found a cure. Virus HIV is attacks the human immune system so that someone is susceptible to disease. This causes if someone is infected with HIV, then the person can experience an danger condition, it will even effect is death. In recent years, the number of children aged 5 – 14 years old that infected with HIV continues to increase. Therefore the author was moved to write about the application of the ARIMA model in forecasting the number of children aged 5 – 14 years old that infected with HIV in Indonesia by 2023. With the hope that the public or the govermment can find out the potential dangers of HIV disease, especially in children aged 5 – 14 years old. So that the public and govermment can jointly eradicate the spread of the HIV virus, especially in chidren. the result are obtained that the model that is suitable for use in forecasting is the ARIMA(0,1,2) models, with error value obtained is 0.057429. with the forecast value of the number of children aged 5 – 14 years old that infected with HIV in Indonesia from 2019 – 2023 in a row is : 570.82, 647.12, 734.14, 823.85, 944.83.